How do assessments of activities of daily living address executive functions: A scoping review. Issue 5 (4th July 2017) - Poncet, Frédérique; Swaine, Bonnie; Dutil, Elisabeth; Chevignard, Mathilde; Pradat-Diehl, Pascale
ABSTRACT: Executive functions (EF) allow persons to adapt to situations arising in daily life and can be affected following acquired brain injury (ABI). Measuring the impact of EF impairments on the accomplishment of activities of daily living (ADL) requires specific assessment tools, but choosing the right tool may be difficult. Purpose : To conduct a scoping review on how assessments of ADL address EF and EF impairments in persons with ABI. Method : A scoping review of literature (peer-reviewed and grey literature) published until August 2014 was conducted. Using a systematic procedure, literature was selected, results were charted, and tools were analysed with respect to their goals, underlying models, psychometric properties and applicability. The analysis also included how tools considered components of EF according to Lezak's model. Results: 12 tools, developed either to assess EF in ADL, independence in ADL considering EF or ADL capacities, were identified and analysed according to multiple criteria. Conclusions : This review provides important information about existing tools to assist in tool selection and clinical decision-making related to ABI and EF.